NEED ANALYSIS OF ENGLISH COURSE OF THE STUDENTS OF UNISKA KEDIRI - M. Syaichul Muchyidin; Wildan Isna Asyhar; Irwan Sulitiyanto (STKIP Pembangunan Indonesia Makassar, 2022)
English is one of courses that must be studied in UNISKA Kediri and it is one of obligation subject of national curriculum at UNISKA Kediri. All faculties have this course to develop the quality of the students and different faculty has their purpose itself, so the English they use called English for Specific Purpose (ESP). English for Specific Purpose (ESP) is the course to get the goal based on the faculty. To get the goal, it needs the analysis of the goal. in other word, different faculty must be different goal. the research uses qualitative approach which describes the phenomenon faced. To get the data, it needs some instruments; such as document and doing interview. The rubrics or the data evaluation here is the goal of material, to know the goal of the material and the method used, the researcher gets from the students of UNISKA Kediri, and the subjects are the students of UNISKA Kediri. The results of the research shows that every faculty has its own interest of English to support their quality, so here are the results (1) Functional Language Use; (2) language Material must contain basic grammar on arranging the structure of sentence, expression use, and vocabulary use based on their faculty or study program; (3) the ability of language use containing reading, writing, listening, and speaking ;namely, reading 35%, writing 25%, listening 20%, and speaking 20%; (4) the use of teaching method, constructivism approach.